Variation of intrapartum care and cesarean rates among practitioners attending births of low‐risk, nulliparous women. Issue 2 (12th February 2020) - Iobst, Stacey E.; Storr, Carla L.; Bingham, Debra; Zhu, Shijun; Johantgen, Meg
Abstract: Background: Variation in hospital cesarean birth rates across the United States is likely because of differences in practitioner practice patterns. Yet, few studies conducted in the last twenty years have examined the relationships between practitioner characteristics and the use of intrapartum interventions and cesarean birth. The objective of this study was to examine associations among practitioner characteristics and the use of amniotomy, epidural, oxytocin augmentation, and cesarean birth in low‐risk women with spontaneous onset of labor. Methods: A secondary analysis was performed using data collected by the Consortium on Safe Labor. The sample included nulliparous term singleton vertex (NTSV) births with spontaneous onset of labor (n = 13 196) from 2002 to 2007 across eight hospitals. Generalized linear mixed models were conducted to examine outcomes. Results: The cesarean birth rate ranged from 7.2% to 18.9% across hospitals and from 0% to 53.3% across physicians. Practice type ( P < .05) and specialty type ( P < .0001) were associated with physician cesarean birth rates. Compared with obstetrician/gynecologists, midwives were nearly twice as likely to use no intrapartum interventions (relative risk 1.80 [CI 95 1.45‐2.24]) and 26% less likely to use amniotomy‐epidural‐oxytocin (0.74 [0.62‐0.89]). Family practice physicians had a 21% lower likelihood of using amniotomy‐epidural‐oxytocin (0.79 [0.67‐0.94]) and a 53% lower likelihood of performing cesarean births (0.47 [0.35‐0.63]). Conclusions: Wide variation in hospital and physician cesarean birth rates was observed in this sample of low‐risk, nulliparous women. Practitioner practice type and specialty were significantly associated with the use of intrapartum interventions. Interprofessional practitioner education could be one strategy to reduce variation of intrapartum care and cesarean birth.